Peran PKBM Al-Abrar dalam Memberantas Buta Aksara Di Masyarakat Desa Bontobulaeng Kabupaten Bulukumba - Yuliartati Yuliartati; A. Firdaus (Publikasi dan UKI Toraja Press Universitas Kristen Indonesia Toraja, 2022)
This research was carried out at PKBM Al-Abrar, Bonto Bulaeng Village, Bulukumpa District, Bulukumba Regency. The purpose of the study was to determine the role of Al-Abrar PKBM in eradicating illiteracy in the Bonto Bulaeng Village Community, Bulukumpa District, Bulukumba Regency. Thisresearch used a qualitative descriptive approach, data collection was carried out using observation, interviews, and documentation methods. Analysis of the data used is qualitative data analysis with data collection steps Data reduction, data presentation, and drawing conclusions. The results of this study are the role of the Al-Abrar Community Learning Center in eradicating illiteracy in the community of Bonto Bulaeng Village, Bulukumpa District, Bulukumba Regency, namely, 1) Reducing illiteracy rates, 2) Increasing reading and writing skills, 3) Increasing numeracy skills. research on the role of the Al-Abrar Community Learning Activity Center in eradicating illiteracy in the community of Bonto Bulaeng Village, Bulukumpa District, Bulukumba Regency. shows that the importance of the role of the AL-Abrar Community Learning Activity Center as a non-formal educational institution that provides lifelongeducation services for the community, especially the illiterate, so that they have the ability to write, read and count, which are oriented to everyday life by utilizingthe potential that exists in the community. surrounding environment.